농산어촌의 지역가치 제고를 위한 공간디자인 사례연구 - 장영호(Young Ho Jang) (한국디자인리서치, 2025)
본 연구는 농산어촌 공간에 대한 포용적 공간디자인 관점에서의 지역 디자인의 발전적 방향을 모색하기 위하여 국내외 농산어촌과 도시의 유휴공간 개선 사례를 분석하였고, 유휴공간이 지역 공동체의 문화자산과 정체성을 반영하는 창조적 거점임을 확인하였다. 주민 참여와 지역 문화 맥락을 반영한 디자인 전략이 공간 전환과 지역 정체성 회복에 기여하며, 농산어촌 사례는 교육·복지·소득 창출이 결합된 포용적 공공 거점의 가능성을 보여준다. 주민 참여, 문화예술 융합, 기능 복합화 및 지속가능성 확보가 지역활성화의 핵심이며, 이를 통합한 공간디자인 전략이 지역사회 회복과 발전에 기여할 수 있음을 강조한다. This study analyzes domestic and international cases of idle space revitalization in rural, mountain, and fishing villages as well as in urban areas to explore progressive directions for regional design from the perspective of inclusive spatial design in rural contexts. The analysis confirms that idle spaces can serve as creative hubs that reflect the cultural assets and identity of local communities. Design strategies that incorporate resident participation and the local cultural context contribute to spatial transformation and the restoration of regional identity. Rural cases demonstrate the potential of inclusive public hubs that integrate education, welfare, and income generation. Resident engagement, cultural and artistic integration, multifunctionality, and the pursuit of sustainability are identified as key elements of regional revitalization, and the study emphasizes that spatial design strategies that holistically integrate these elements can significantly contribute to the recovery and development of local communities. KCI Citation Count: 0